Blue-tooth based remote robot controller - Ye Myint. (2009)
This thesis presents the design of a Blue-tooth based remote robot, which can follow a target object using a fixed single camera. This design emphasizes on the vision-base target tracking control with suitable software and hardware structures. The target tracking based on a 3-D position estimation uses a single camera with robot motion control algorithm, which is analyzed and implemented in a low-cost manner. The performance of the system is verified for the robustness analysis for the designed algorithms.